2018
DOI: 10.5344/ajev.2018.17067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Yeast Flocculation and Biofilm Formation on Yeast-Fungus Coadhesion in a Novel Immobilization System

Abstract: A novel method of yeast immobilization, called "biocapsules", has been developed in which cells of the yeast Saccharomyces cerevisiae become attached to the hyphae of the fungus Penicillium chrysogenum, remaining adhered following loss of viability of this fungus. Yeast immobilization facilitates higher cell densities than traditional fermentation methods, improves yield, and allows the reuse of the biocatalyst. Yeast cells may adhere to each other via specific cell-surface molecular interactions (flocculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
5
9
0
1
Order By: Relevance
“…Biocapsule number and diameter are indistinguishable for FLO11 when expressed from either the ADH2 or HSP30 promoters, but the level of attachment of the cells varies dramatically (Figure 1C ), suggesting that strain parameters but not the physical action of attachment dictate biocapsule number and diameter. Moreno-García et al (2018b) supports this result with an earlier experiment and found that mass and volume of yeast biocapsules are highly strain dependent.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Biocapsule number and diameter are indistinguishable for FLO11 when expressed from either the ADH2 or HSP30 promoters, but the level of attachment of the cells varies dramatically (Figure 1C ), suggesting that strain parameters but not the physical action of attachment dictate biocapsule number and diameter. Moreno-García et al (2018b) supports this result with an earlier experiment and found that mass and volume of yeast biocapsules are highly strain dependent.…”
Section: Resultssupporting
confidence: 90%
“…The ability of Flo proteins to be able to adhere to neighboring cells or other substrates may also explain the trend of large size but few in number of biocapsules (Figures 4 – 6 ). This linear regression matches with that of a previous study by Moreno-García et al (2018b) , where biocapsules made with different wild type yeast strains displayed large-few or small-abundant trends. Overexpressed FLO11 strains resulted in the largest diameter biocapsules perhaps because Flo11p allows for attachment with a longer retention and more permanency compared to Flo1p and Flo5p which are involved in flocculation only and no other FLO11 phenotypes, where attachment is easily broken by intense agitation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Even after complete fermentation, the biocapsules maintain their integrity which makes possible to reuse them for subsequent fermentations (Peinado et al 2006). Further, the biocapsules have been investigated to have high immobilization efficiency up to 84% yeast cell immobilized (Moreno-García et al 2018b) and unlike most immobilization methods, yeast biocapsules can prevent loss of cells from the carrier because of potential attachment of any newly formed daughter cells using the same natural process as the attached parental cells (Moreno-García et al 2018c). What determines the specific mechanism of attachment is still in question, but studies have shown that different yeast strains affect immobilization ability.…”
Section: Introductionmentioning
confidence: 99%